2021
DOI: 10.1039/d1sc03860e
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic enantioselective synthesis of 1,4-dihydropyridines via the addition of C(1)-ammonium enolates to pyridinium salts

Abstract: The regio- and stereoselective addition of C(1)-ammonium enolates – generated in situ from aryl esters and the isothiourea catalyst (R)-BTM – to pyridinium salts bearing an electron withdrawing substituent in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 164 publications
(53 reference statements)
2
13
0
Order By: Relevance
“…The use of alternative aryl esters was next probed, with pentafluorophenyl ester 2 and bis(trifluoromethyl)phenyl ester 3 giving amide products 7 and 8 in high yield, but with lower enantioselectivity than when using PNP ester 1 (Entries 4 and 5). The use of 2,4,6-trichlorophenyl ester 4 resulted in only 31% yield (Entry 6), which is consistent with previous studies in this field [65,72,76,79], and most likely reflects the increased steric hindrance of the aryloxide attenuating its nucleophilicity. Finally, using PNP ester 1, the catalyst loading could be reduced to 5 mol% with only a small drop in stereoselectivity (Entry 7), while heating the reaction to 40 • C provided a slight improvement in yield (Entry 8).…”
Section: Reaction Optimizationsupporting
confidence: 89%
See 2 more Smart Citations
“…The use of alternative aryl esters was next probed, with pentafluorophenyl ester 2 and bis(trifluoromethyl)phenyl ester 3 giving amide products 7 and 8 in high yield, but with lower enantioselectivity than when using PNP ester 1 (Entries 4 and 5). The use of 2,4,6-trichlorophenyl ester 4 resulted in only 31% yield (Entry 6), which is consistent with previous studies in this field [65,72,76,79], and most likely reflects the increased steric hindrance of the aryloxide attenuating its nucleophilicity. Finally, using PNP ester 1, the catalyst loading could be reduced to 5 mol% with only a small drop in stereoselectivity (Entry 7), while heating the reaction to 40 • C provided a slight improvement in yield (Entry 8).…”
Section: Reaction Optimizationsupporting
confidence: 89%
“…The enantioselectivity of the transformation indicates the C-C bond forming event takes place on the Si-face of the ammonium enolate. This selectivity can be rationalized through preferential formation of the (Z)-ammonium enolate [76][77][78][79]85], which is conformationally-restricted by an intramolecular 1,5-O• • • S interaction [61,[88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104] and results in the phenyl stereodirecting group of the catalyst blocking the enolate Re-face. The observed poor diastereoselectivity can be tentatively rationalized by a simple stereochemical model that assumes a favored, open pre-transition state assembly where steric interactions are minimized about the forming C-C bond.…”
Section: Proposed Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, the group of Smith has studied the synthesis of 1,4-dihydropyridines 120 by addition of aryl ester 105 to N-alkyl pyridinium salts 47 bearing an electron-withdrawing group at the 3-position catalyzed by (R)-BTM isothiourea chiral catalyst C25 (Scheme 37). [78] In the presence of 20 mol% of C25, 1.5 equivalent of DABCO in toluene at 0 °C, the reaction proceeded smoothly to provide several 1,4-addition products in low to moderate isolated yields (29-70%), good diastereoselectivities (80:20 to 95:5 dr) and variable level of enantioselectivity (0-96% ee) (Scheme 37a). For stability purposes, the 1,4addition product 120 bearing a phenolic moiety must be transformed into the corresponding amide prior to purification by treatment of the crude mixture with amine nucleophile (benzyl amine, piperidine, morpholine or N-Boc piperazine) (Scheme 37b).…”
Section: Pyridinium Saltsmentioning
confidence: 99%
“…In addition, some interesting features were noticed by the authors: 1) contrarywise to most others reported approaches which have been shown to be sensitive to variation of the EWG group of the pyridinium salt, CN, PhSO2 and CO2Et-substituted pyridinium salts were efficient in terms of reactivity and selectivity (except for CO2Et which result in the production of a racemate); (2) the R 1 group must be a benzyl (pyridinium salt with Me substituent being unreactive) presumably to provide stabilization of the transition state thanks to - or cation interactions; (3) the nature of the counter-cation of the pyridinium salt is crucial for the reaction to occur. Non-coordinating anions (BF4 or PF6) were less efficient both in Very recently, the group of Smith has studied the synthesis of 1,4-dihydropyridines 120 by addition of aryl ester 105 to N-alkyl pyridinium salts 47 bearing an electronwithdrawing group at the 3-position catalyzed by (R)-BTM isothiourea chiral catalyst C25 (Scheme 37) [78]. In the presence of 20 mol% of C25, 1.5 equivalent of DABCO in toluene at 0 • C, the reaction proceeded smoothly to provide several 1,4-addition products in low to moderate isolated yields (29-70%), good diastereoselectivities (80:20 to 95:5 dr) and variable level of enantioselectivity (0-96% ee) (Scheme 37a).…”
Section: Pyridinium Saltsmentioning
confidence: 99%